From Centralized Control to Adaptive Governance: Reforming Cultural Management in Azerbaijan - Aliyeva, Laman; Zeynalova, Rasima; Naghizada, Nazrin (ADA University, 2025)
This paper addresses the reform demands of cultural administrations in Azerbaijan, highlighting important challenges, mostly resulting from governance inefficiencies, a lack of financial resources, infrequent public participation, and an overall delay in digital transformation. Historically embedded in a centralized model from the Soviet Union, cultural institutions in Azerbaijan continue to meet self-imposed limitations that restrict their innovation, responsiveness, or adaptability to global cultural trends. Financial overdependence on state funding makes this sector vulnerable to economic shocks and restricts the continuity and growth referenced above. Quite often, exclusionary governance practices mean low public engagement and cultural relevance, while imbalanced digital infrastructures keep them uncompetitive internationally, while limiting audience expansion. It largely applies qualitative methods in the comparative study of successful international models, such as those in Germany, the Netherlands, and Estonia. It elicits key interventions, including: Decentralization of cultural governance; Improvement of the public-private partnership relation to create an alternative source of financing; Creation of participatory governance framework; and speeding up the digital transformation. This policy proposes comprehensive reform measures that promote reform at the internal structures to allow local institutions to take ownership of their budgets; financing arrangements that guarantee sustainability; mechanisms for public engagement for enhanced transparency and inclusiveness; and considerable investment in digital capabilities. With these strategic reforms, the Azerbaijan cultural institutions shall dismantle the limitations posed by their history, thus preserving national heritage effectively and positioning themselves as resilient and innovative entities capable of thriving in a rapidly evolving global cultural landscape.
Keywords: Cultural policy -- Azerbaijan; Cultural institutions -- Azerbaijan; Public administration -- Azerbaijan; Public-private sector relations; Cultural institutions -- Governance -- Public participation -- Innovation; Heritage preservation -- Management -- Sustainability -- Public engagement.; Public and International Affairs